PELATIHAN DAN PENDAMPINGAN MEDIA PEMBELAJARAN POWERPOINT BASED ON ANDROID PADA MAHASISWA CALON GURU - Sukroyanti, Baiq Azmi; Habibi, Habibi; Herayanti, Lovy; Putrayadi, Wirawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The policy of learning activities in the midst of technological advances based on Android requires teachers to create interactive and effective learning. One of the learning components that teachers must have is mastery of interesting, interactive, and effective learning media that can be applied in the classroom both offline and online. Therefore, the purpose of service is to help and facilitate prospective teachers in mastering learning media by utilizing android applications so that they can be applied to students. The method applied is training and mentoring in creating and applying Android-based Pawerpoint learning media. These results are expected to provide information in varying the use of interactive learning media that can be implemented in the classroom. In addition, this PowerPoint based on Android learning media is expected to be able to assist teachers in creating interactive and fun learning activities so that students are able to achieve the desired learning competencies.